2009
DOI: 10.1667/rr1684.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Radiation-Induced Single-Strand Breaks in Plasmid DNA using a TUNEL/ELISA-Based Assay

Abstract: To accurately quantify the number of single-strand breaks (SSBs) induced in plasmid DNA molecules after irradiation, a new type of assay methodology has been explored. The new method is based on the TUNEL (terminal deoxynucleotide transferase dUTP nick end-labeling) assay that was adopted for use under ELISA (enzyme-linked immunosorbent assay) conditions. The assay was found to both improve the quantification and reduce the uncertainties in measurement of SSBs compared with the commonly used agarose gel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A variety of types of DNA damage, including single-strand breaks, double-strand breaks and base damage, occur in response to radiation, and the DNA repair process is activated to address such damage. However, high-dose radiation can induce extensive DNA damage that is difficult to repair and might interfere with cell cycle progression, at which point cells undergo programmed cell death [16], [17], [31]. Adaptive protection against DNA damage and bystander effects might also occur in response to low-dose radiation, generally in terms of the protective mechanisms associated with hormesis [11], [15], [32], [33].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of types of DNA damage, including single-strand breaks, double-strand breaks and base damage, occur in response to radiation, and the DNA repair process is activated to address such damage. However, high-dose radiation can induce extensive DNA damage that is difficult to repair and might interfere with cell cycle progression, at which point cells undergo programmed cell death [16], [17], [31]. Adaptive protection against DNA damage and bystander effects might also occur in response to low-dose radiation, generally in terms of the protective mechanisms associated with hormesis [11], [15], [32], [33].…”
Section: Discussionmentioning
confidence: 99%
“…This type of plasmid has already been widely used in irradiation studies [16,17]. NaOH was chosen to stabilize plasmid DNA under vacuum conditions as it was shown that a lack of cations in the vicinity of phosphate backbone in DNA solution prior to solvent evaporation leads to DNA strand breaks and is due to constituent water removal from DNA [18].…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…Such a simplification can be used in case of low P S values and it was shown that for investigations of hydroxyl radical attack [55] that this condition was fulfilled, thus the model may be implemented for DNA damage modelling. In addition, when this simplified case is being analysed, and the distribution of SSBs between two DNA strands is not being distinguished but treated as equally distributed between the two stands, the accumulation of DSBs as a result of SSBs accumulation, P DS , can be written as [20] …”
Section: Obtaining the Basic Parameters Of Dna Damage Through Fittingmentioning
confidence: 99%
“…Therefore, to accurately determine the level of SSBs in samples that have been exposed to VUV radiation, an alternative analysis method based on the TUNEL (Terminal deoxynucleotide transferase dUTP Nick End Labelling) assay, which is used for SSB labelling with a fluorescent probe in cellular DNA to detect apoptotic cells [69] was developed [55]. In this work, the assay has been translated into an ELISA (Enzyme-Linked ImmunoSorbent Assay) -based conditions, in which purified DNA immobilised on plates can be used instead of cells.…”
Section: Vuv Induced Damage In Dnamentioning
confidence: 99%
See 1 more Smart Citation